Endothelial dysfunction and C‐reactive protein predict the incidence of heart failure in hypertensive patients. (25th November 2020) - Maio, Raffaele; Perticone, Maria; Suraci, Edoardo; Sciacqua, Angela; Sesti, Giorgio; Perticone, Francesco
Abstract: Aims: Endothelial dysfunction and heart failure are associated, but no prospective studies demonstrated that impaired endothelium‐dependent vasodilation predicts incident heart failure. We designed this study to test whether endothelial dysfunction is associated with incident heart failure in a group of hypertensives. Methods and results: We enrolled 735 White never‐treated hypertensive outpatients free from heart failure, diabetes, chronic kidney disease, and previous cardiovascular events. Endothelium‐dependent vasodilation was investigated by intra‐arterial infusion of acetylcholine, and laboratory determinations were obtained by standard procedures. During the follow‐up [median 114 months (range 26–206)], there were 208 new cases of heart failure (3.1 events/100 patient‐years). Dividing the study population in progressors and non‐progressors, we observed that progressors were older, showed a higher prevalence of being female, and had a higher baseline heart rate, glucose, insulin, Homeostatic Model Assessment (HOMA), creatinine, and high‐sensitivity C‐reactive protein (hs‐CRP) mean values, while estimated glomerular filtration rate and maximal acetylcholine‐stimulated forearm blood flow were lower. In the multiple Cox regression analysis, female gender [hazard ratio (HR) = 1.454, 95% CI = 1.067–1.981], fasting glucose (HR = 1.186, 95% CI = 1.038–1.357), hs‐CRP (HR = 1.162, 95% CI = 1.072–1.259), HOMA (HR = 1.124, 95% CI = 1.037–1.219), acetylcholine‐stimulated forearm blood flow (HR = 0.779, 95% CI = 0.695–0.874), and estimated glomerular filtration rate (HR = 0.767, 95% CI = 0.693–0.849) maintained an independent association with the outcome. Successively, testing the interaction between forearm blood flow and hs‐CRP, we observed that patients who have hs‐CRP values above the median and forearm blood flow under the median show a higher risk of developing heart failure (HR = 7.699, 95% CI = 4.407–13.451). Conclusions: The present data demonstrate that an impaired endothelium‐dependent vasodilation and hs‐CRP predict development of incident heart failure in hypertensives.